Uncovering the wide protective responses in Coffea spp. leaves to single and superimposed exposure of warming and severe water deficit - Rodrigues, Ana P. (2024)
Funding Information: Fellowships from the Conselho Nacional de Desenvolvimento Científico e Tecnológico, Brazil (CNPq) (EC, FP, FD), and the Fundação de Amparo à Pesquisa do Estado de Minas Gerais, Brazil (FAPEMIG, project CRA-RED-00053-16, APQ01512-18) (FD), and the Fundação de Amparo à Pesquisa e Inovação do Espírito Santo (FAPES, proc. 2022-M465D) (MR) are also greatly acknowledged. Publisher Copyright: Copyright © 2024 Rodrigues, Pais, Leitão, Dubberstein, Lidon, Marques, Semedo, Rakocevic, Scotti-Campos, Campostrini, Rodrigues, Simões-Costa, Reboredo, Partelli, DaMatta, Ribeiro-Barros and Ramalho.